PERANAN PROGRAM TADARUS AL-QUR’AN DALAM MENANAMKAN MINAT BACA AL-QUR’AN PESERTA DIDIK DI MAN 1 POLEWALI MANDAR - Ruhaya, Besse; Baharuddin; Muhammad Lutfi (Inspiratif Pendidikan, 2023)
This study aims to find out and describe: 1) The interest in reading the Qur'an of students in MAN 1 Polewali Mandar. 2) The function of the tadarus al-Qur'an program is to instill interest in reading the Qur'an for students at MAN 1 Polewali Mandar. 3) Supporting and inhibiting factors of the Qur'an tadarus program in instilling interest in reading the Qur'an of students at MAN 1 Polewali Mandar. This type of research is field research with a qualitative approach and descriptive method located at MAN 1 Polewali Mandar. The primary data sources of this study were the Deputy Head of Madrasah for Student Affairs (key informant) and two teachers and five students (additional informant). Secondary data sources of this research are books, journals and the internet. The data collection methods used are observation, interview and documentation methods. Analysis of research data by data reduction, data presentation, and conclusion drawing. The results of this study found that the interest in reading the Qur'an of students at MAN 1 Polewali Mandar was quite high. The supporting factors are good cooperation between all parties in MAN 1 Polewali Mandar, support and encouragement from parents of students, quality human resource conditions and adequate facilities and infrastructureThe function of the Qur'an tadarus program is to form the habit of reading the Qur'an in students, so that in students there is an interest in reading the Qur'an. Inhibiting factors are the number of students who are very large and diverse, the place of implementation of the Qur'an tadarus program which is outdoors so that it is often hampered when it rains and the awareness of parents who are still lacking in giving examples to their children about reading the Qur'an